Prognostic Factors in Patients with Clinic Locally Advanced T4 Lung Cancer: Surgical Considerations - Kaba, Erkan; Cosgun, Tugba; Yardimci, Halit; Toker, Alper (The Thoracic and Cardiovascular Surgeon, 2022)
Background Inclusion of surgery in the treatment of T4 lung cancer has been a debate for the last two decades. The aim of this study is to investigate the potential prognostic factors which could affect the outcome.Methods Fifty-seven clinical T4 non-small cell lung carcinoma (NSCLC) patients out of 716 lung resections, who were operated at a single institution in 7 years period, were included in this study. Patients are grouped into three groups as patients with neoadjuvant treatment group (group 1 n: 16), salvage surgery group (surgery after 3 months of definitive chemotherapy and radiotherapy) (group 2 n: 14), and straightforward surgery group (group 3 n: 27) with adjuvant treatment. Groups were analyzed and compared in terms of postoperative complications, 30 days of mortality, disease free survival, and overall survival.Results Mean overall survival (OS) was 48.43 ± 4.4 months and mean disease-free survival (DFS) 40.55 ± 4.46 months for all patients. Thirty days mortality was 5.2% and complication rates were 63.1%. Two years OS was 61.4 ± 6.4%, DFS was 58.1 ± 7.8%. Group 1, Group 2, and Group 3 patients had mean 39.14 ± 5.6, 44.7 ± 7.1, and 62.9 ± 4.8 months for OS (p: 0.09), and 29.6 ± 7.2, 38.4 ± 9.1, and 46.9 ± 6 months for DFS (p: 0.27). Patients who received blood transfusion showed significantly worse outcomes (p: 0.001 for DFS and p: 0.004 for OS).Conclusion According to our outcomes, surgery should be included in the treatment of clinical T4 lung cancer when physiologically and oncologically possible with careful patient selection. This study demonstrates that patients receiving straightforward surgery have longer survival, in spite of higher perioperative mortality rate. Risks and benefits should be considered carefully.
Keywords: non-small cell lung cancer; TNM staging; T4 tumor